Authenticity: A very Greek word in a complex European setting - Dimitrios Zygomalas (Ochrona Dziedzictwa Kulturowego, 2025)
A focal point in present-day conservation terminology, authenticity comes from the ancient Greek word afthentikós, which in modern times has come to mean genuine and valid. Based on this interpretation, it entered the conservation agenda, through the Venice Charter, in 1964, received added attention, through the Nara Document, in 1994, and since then, has generated multiple debates among conservation specialists. Yet while a wide consensus on a definition and method of assessment of authenticity pends, other key players in the European setting, namely national authorities, separate bodies, public groupings, and individual owners endorse, and in many cases, assume action in opposite directions. Considering the practical impact of these contradictions, the overall issue needs to be urgently discussed, which is precisely the goal of this paper. Based on extensive bibliographic and archival research, it initially addresses the evolution of the term “authenticity” and its current standing in the conservation agenda. It then examines and evaluates the aforementioned opposite postures, with reference to characteristic examples throughout Europe, and concludes by outlining proposals for the necessary reconciliation.